Fahr's syndrome (Bangladesh Medical Journal Khulna, 2013)
Miss Merry, 17 years old girl hailing from Barobila., Patkelghata, Satkhira was admitted in Khulna Medical College Hospital on 27-06-2010 with the complaints of fever, convulsion and unconsciousness for 7 days. She has also some hearing impairment, behavioral abnormalities and stunted growth since her childhood. On examination she was deeply unconscious, anaemic and febrile. CT scan of brain reveals multiple bilateral symmetrical calcification seen in the brain parenchyma involving basal ganglia, thalamus, para ventricular region, and cerebellar nucleus. Multiple ill defined hypodense areas are seen in the both parieto-occipital region, suggestive of Fahr's syndrome with meningoencephalitis. DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13628 Bang Med J (Khulna) 2012; 45 : 33-35